Antibacterial Activity Test of Passiflora Foetida Linn Leaves Extract on Propionibacterium Acne - Arni, Veni Zafi; Irwandi, Irwandi; Hardia, Lukman (Newinera Publisher, 2024)
Acne is a chronic inflammatory skin disease affecting the sebaceous glands, primarily caused by the growth of Propionibacterium acne. A significant natural antibacterial agent against the bacteria is Rambusa (Passiflora foetida Linn) leaves, which contain active compounds such as alkaloids, flavonoids, tannins, saponins, and terpenoids/steroids. Therefore, this research aimed to evaluate antibacterial activity of ethanol extract from Rambusa leaves against Propionibacterium acne growth and determine the effective concentration of test solution inhibiting bacteria growth. The leaves were subjected to extraction through the maceration method using 96% ethanol solvent. The resulting extract was tested for antibacterial activity using the disc diffusion method. This research used three concentrations, including 10% b/v, 15% b/v, and 20% b/v. The positive control used 2 µg clindamycin disks, and the negative control used aqua pro injection. The analysis results showed that there was no clear zone area around disks containing Rambusa leaves extract at any concentration. In conclusion, the ethanol extract of leaves lacked antibacterial activity against Propionibacterium acne.